Ethical Integration of Generative AI and Students’ Motivation in Academic Writing: An Exploratory Practice in an Islamic Higher Education Context - Adara, Reza Anggriyashati; Victorynie, Irnie; Hidayati, Istiqlaliah Nurul; Rosyid, Abdul; Hidayati, Poppy Sofia (Register Journal, 2026)
This study investigates the ethical integration of generative Artificial Intelligence (AI) and its impact on students’ motivation and academic writing in an English for Academic Purposes (EAP) course at an Islamic higher education institution in Indonesia. The study conceptualizes Islamic values, particularly academic integrity, responsibility, and authorship, as essential competencies in second language academic writing. Forty undergraduate students were divided into experimental and control classes. In the experimental class, students collaboratively formulated classroom guidelines for responsible AI use through focus group discussions, which were implemented over seven sessions using an Exploratory Practice approach. Reflective essays written before and after AI integration were analyzed thematically, and writing performance was assessed using IELTS criteria. The findings indicate that generative AI supported surface-level writing skills such as grammar, vocabulary, and coherence; however, higher-order skills, including critical thinking, idea development, and appropriate use of references, declined when AI was employed without sufficient pedagogical guidance. Students reported increased efficiency alongside concerns about over-reliance, emphasizing that AI should function as a supportive tool rather than a substitute for individual effort. Comparisons with the control class show that conventional instruction led to steady improvement in writing, whereas AI integration produced mixed outcomes, highlighting the need for ethical guidance. The study demonstrates the importance of thoughtfully integrating AI in Islamic higher education to promote both academic proficiency and ethical responsibility, and it contributes to ELT research by linking Islamic academic values with responsible language learning and authorship practices.